THE SOCIAL AND ECONOMIC IMPACT OF ‘SWACCH BHARAT ABHIYAAN’ ON RURAL WOMEN IN INDIA (STUDY WITH FOCUS ON VILLAGES IN WEST BENGAL) - Mehta, Vibha (Digital Repository of Theses, 2023)
There has been a long pending and dire need for the social and economic upliftment of women in rural India. Open defecation leads to several social, psychological, economic and medical problems in women of rural India. This study aims to assess the effectiveness of the Swach Bharat Abhiyan vis-à-vis various parameters of women’s social and economic empowerment like literacy, employment, overall quality of life etc. Information was collected from women and schools of villages in West Bengal, India regarding parameters like household incomes, expenses, perceived security, girls’ literacy etc. This information was then collated and analysed statistically to derive conclusions regarding the existence of any correlations between the Swachh Bharat Abhiyan and any improvement/decline in the social and economic status of rural women in India. The findings of the study indicate a positive social impact of the Swach Bharat Abhiyan on rural women. 85 percent of women reported a vast improvement in their quality of life, sense of security etc. Other social parameters measuring girls’ literacy like attendance rates etc. also showed an improvement as a result of the implementation of the program.This study’s findings, with regards to the economic impact of the Swach Bharat Abhiyan on rural women in India, were largely inconclusive, however. Only 10 percent of the women reported a rise in household income attributable to the construction of toilets while 95 percent reported a rise in expenses related to their upkeep and maintenance. The data regarding indirect medical expenses was also quite ambiguous with a little more than half the respondents claiming a decline in medical expenses related to the impact of the Swach Bharat Abhiyan and the remainder reporting a rise in medical costs, albeit reasons provided were unrelated to the program.Another finding of the study was the largely unexplored aspect of the ecological advantage of this mission 80 percent of the respondents were unaware of the possibility of utilizing toilet wastes as fertilizers or biogas. Further research may be conducted to explore the economic and ecological benefits of the Swach Bharat Abhiyan so that it positively impacts the overall quality of life of all Indian women.